Intracellular Ca2+ signaling: calcium influx - Parekh, Anant (Henry Stewart Talks, 2007)
Importance of intracellular calcium in cell activation, Sources of intracellular calcium, Key role for calcium channels in the plasma membrane, Voltageoperated calcium channels, Sub-types of voltage-operated calcium channels, Structure of voltage-operated calcium channels, Functions of voltage-operated calcium channels, Local calcium signals drive cellular responses, Store-operated calcium channels, Properties of store-operated channels, CRAC channels, Gating of CRAC channels